Heating Up, Cooling Down: The Moralisation of Markets through Devices and Their Unintended Consequences - Arnold, Nadine; Soppe, Birthe (The International Journal of Sociology of Agriculture and Food, 2025)
Social movements play a critical role in politicising food systems, often contesting and moralising markets to advance their social change agenda. To induce moralisation processes, social movements frequently deploy market devices. Examining the case of the creation and development of the Swiss fair trade flower market over time (1990–2005), we investigate how several market devices are being used in moralising a market, including the intended and unintended consequences of this process. Our findings reveal how the sequencing of devices—the gradual build-up of various devices upon one another—enabled the market-pioneering movement to first ‘heat up’ moral concerns and raise awareness, and later ‘cool down’ these concerns by specifying accountabilities and obligations to scale the market. However, the sequencing of devices resulted in a moralised market concentrated on a powerful device—a certification standard for plantations—which in turn triggered tensions within the fair trade movement. The market pioneers became marginalised, and the initial fair trade idea—supporting smallholders—became fundamentally renegotiated at international level. These findings advance our understanding of the mainstreaming process of fair trade, explain how fair trade has come to encompass its first non-food product (i.e., flowers) and planation production, and contribute to research on movement-induced markets by highlighting the unintended consequences and intra-movement conflicts of building moralised markets through devising.